Mecanismo de oxidação da pirita: uma abordagem através de cálculos DFT - Egon Campos dos Santos (2016)
The knowledge of sulfide minerals and, particularly, the knowledge about pyrite chemical properties has great importance currently. As the most abundant sulfide mineral in the earth's crust, pyrite is the main component of mine wastes. When exposed to atmospheric air gases and humidity its oxidation generates SO4 2-, Fe2+ and H+ species in the medium. The acid formed contributes to acidification of acquifers and beds, and also can leach heavy metals from rocks, contaminating the soil. This phenomenon is called Acid Mine Drainage (AMD) and results inseverous consequences for the environment. Because of this, there are a lot of scientific work focused on understand of pyrite reactivity in the presence of oxygen and water molecules, but in most cases available experimental techniques have no satisfactory results. Theoretical andexperimental methodologies have been employed obtaining great success, establishing a chemical picture on the reactivity of solids at molecular level. Among the theoretical methodologies employed, the DFT has been widely used for providing results according to the experimental observation and, at the same time, it is able to perform calculations with a reasonable computational cost. Therefore, this study was a theoretical study of the reactivity of pyrite in the presence of water and oxygen molecules. Structural, electronic, magnetic and chemical properties of pyrite and its cleavage surface were elucidated. The DFT/PBE/Planewaves methodology employed at this work showed good agreement with the experimental data. The cleavage surface was modeled to assess their reactivity with respect to oxygen and wateradsorbates. The water molecules adsorbed with an energy of -14.5 kcal mol-1, a value close to that is found experimentally (~ -10 kcal mol-1). The adsorption of oxygen was evaluated using different coordination modes with the surface (100) of pyrite. The initial steps of the pyriteoxidation mechanism have been studied. The reactions involving the formation of OH2, O2-, O2 -, OH- and OOH- species were found. With the results obtained, a new interpretation of the oxidation mechanism will be made at the end of this work.